Unusual porous crystals via catenation of 1D ladders: unprecedented mixture effects on the adsorption of xylene isomers in a SCSC mode. Issue 1 (12th November 2020) - Lee, Soojin; Kim, Dongwon; Park, In-Hyeok; Jung, Ok-Sang
Abstract : The pseudo 2D open-channel crystals formed via catenation of 1D ladders show unusual mixture effects on the adsorption of o -, m -, and p -xylene isomers in a SCSC mode, and are a practical template for structural determination of small hydrocarbons. Abstract : Self-assembly of silver(i ) perchlorate with a C 3 -symmetric tridentate N-donor ligand produces stable crystals with open channels via catenation of 1D ladder-type coordination polymers. The open-channel crystal shows both unprecedented mixture and temperature effects on the adsorption and separation of o -, m -, and p -xylene isomers in a single-crystal-to-single-crystal (SCSC) mode. o -Xylene is not adsorbed into the channel at 5 °C, but is inserted into the channel at room temperature. In particular, the 1 : 1 mixture of o - and m -xylene was adsorbed into the channel in the 1 : 1 mole ratio via intermolecular weak interactions at 5 °C. In addition, the porous crystals are a practical template for structural determination of small liquid hydrocarbons in the SCSC state.